CONTRAST-INDUCED NEPHROPATHY IN CARDIOLOGY PRACTICE - O. I. Turenko; A. Yu. Lebedeva; I. G. Gordeev; N. A. Volov (Российский кардиологический журнал, 2011)
Contrast-induced nephropathy (CIN) is an important problem in cardiology practice, due to the wide use of contrast-based diagnostic and therapeutic interventions in cardiac patients. Despite the high annual rates of coronary angiography and various coronary interventions, the problem of contrast-induced renal complications has not been adequately addressed and controlled. This literature review describes the link between CIN and increased risk of morbidity, mortality, and extended hospitalization. Based on the published data, the prevalence of CIN is assessed, and the major pathogenetic mechanisms of CIN are presented, with an emphasis on CIN risk factors. The methods for correction of modifiable risk factors are proposed, as an approach towards CIN prevention. In addition, modern strategies of CIN prevention and their effectiveness are analysed.